VEGF optimizes the formation of tissue-engineered small intestine. (September 2011) - Matthews, Jamil A; Sala, Frédéric G; Speer, Allison L; Warburton, David; Grikscheit, Tracy C
Aim: To determine the effect of VEGF overexpression on tissue-engineered small intestine (TESI) formation.Materials & methods: Organoid units were isolated from the intestines of 2-week-old transgenic mouse pups capable of inducible, ubiquitous VEGF overexpression ( CMV-Cre/rtTA/tet(0)-VEGF ) and implanted into nonobese diabetic/severe combined immunodeficiency mice. Resulting TESI were explanted at 2 and 4 weeks, and studied by histology, tissue ELISA and immunofluorescence.Results: At 2 weeks postimplantation, the TESI mucosa from the VEGF overexpression group formed rudimentary villi and more crypts compared with controls, which demonstrated a flat epithelium with few crypts and no villi. At 4 weeks postimplantation, the TESI from the VEGF overexpression group was larger and significantly heavier than controls. Within the mucosa, the villus height and crypt depth was significantly longer, contained a greater percentage of proliferating crypt epithelial cells and consisted of all four terminally differentiated epithelial cell types. There was also a significant increase in the capillary density within the submucosa.Conclusions: Overexpression of VEGF optimizes the formation of TESI by increasing the submucosal capillary density, crypt epithelial proliferation and the rate of mucosa formation. A larger construct with increased villus and crypt height was noted after 4 weeks in vivo .